THE FAMILY WITHIN THE VALUE SYSTEM AND FAMILY VALUES IN THE CONTEXT OF LATVIA TODAY: INSIGHTS FROM THE EUROPEAN VALUES SURVEY - Koroļeva, Ilze; Pranka, Maruta; Elksne, Ginta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The formation of a person's values and mindset shift is a process that takes place throughout a person's life, but views on basic values are instilled in the family from early childhood and their formation continues during the socialisation process at school and in society. The family plays a primary role in the transmission of values as important elements of an individual's character, the teaching of which largely determines the individual's life path. Just as family structures have changed over time and vary from culture to culture, so too have attitudes towards the family, its relationship to society and its relative value in the social order. This paper analyses the place of the family as a value in the overall value system of the individual and identifies the value beliefs that currently prevail within the family itself. The main research questions to be answered are: (1) are there differences in views – and what are these differences – on the value of the family among different groups in Latvian society; (2) what values are transferred in the family and passed down to children? The analysis of the problem is based on Latvian data from the fifth phase of the European Values Survey (EVS) in 2021 (n=1335).